The Importance of Corporate Reputation in Reducing Stock Return Volatility: Evidence toward SDG 16 - Isnayni Sabila; Rahmawati Rahmawati; Endang Dwi Amperawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To examine the effects of trading volume activity and earnings quality on stock return volatility and investigates the moderating role of corporate reputation in non-cyclical consumer companies listed on the Indonesia Stock Exchange. The study also highlights the contribution of corporate reputation to sustainable capital market stability in line with SDG 16. Method: Using a quantitative approach with secondary data from non-cyclical consumer companies during 2017–2021. Hypotheses were tested using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Results: The results show that trading volume activity positively affects stock return volatility, while earnings quality negatively affects stock return volatility. Furthermore, corporate reputation weakens the positive effect of trading volume activity on volatility and strengthens the negative effect of earnings quality on volatility, thereby contributing to lower market uncertainty and greater stability. Novelty: Extending prior research by incorporating corporate reputation as a moderating variable in the relationship between trading volume activity, earnings quality, and stock return volatility. The findings provide evidence from an emerging market context and demonstrate the role of corporate reputation in reducing market risk and supporting sustainable capital market development.